Etiopathogenetic patterns of blepharoptosis in Western Nepal : an Overview - Gautam, Pragati; Adhikari, Risihant; Sharma, Basanta Raj (Nepalese Journal of Ophthalmology, 2016)
Background: The clinical picture of blepharoptosis varies from a cosmetic problem to severe visual dysfunction depending on the pathogenesis and the degree of ptosis. Objective: To study the type, pattern and causes of ptosis in patients seeking oculopastic care in western Terai of Nepal Patients and methods: A retrospective descriptive hospital based was carried out over a period of 2 years in oculoplastic clinic in Lumbini Eye Institute, Bhairahawa. Demographic variables including the age of the patient, gender, laterality of the eye(s), visual acuity, presence of refractive error and or amblyopia, type of ptosis and previous ptosis surgery were recorded. Results: There were altogether 326 patients of ptosis during the 2 year-period. Congenital ptosis presented early the mean age being 23(SD ±9.91) years. Acquired ptosis presented late with the mean age of 35(SD± 14.98) years. Congenital ptosis was more common (52%) compared to acquired ptosis (48%). 4.7% of congenital ptosis had amblyopia. Among all ptosis patients, myogenic cause of ptosis was the commonest followed by mechanical, aponeurotic, traumatic and neurogenic. Simple congenital ptosis was the commonest, and among acquired ptosis, mechanical ptosis was the commonest. Most of the ptosis was unilateral (87.7%) regardless of its onset either congenital or acquired. Regarding the severity of ptosis, mild ptosis was the commonest. Conclusion: Ptosis was the 3rd most common lid condition in oculoplastic clinic presentation after entropion and chalazion. Simple congenital ptosis was the commonest form of ptosis. Nepal J Ophthalmol 2016; 8(15): 36-40